#### 2.374   ODE No. 374

$y'(x)^2-2 y'(x)-y(x)^2=0$ Mathematica : cpu = 0.0701045 (sec), leaf count = 73

$\left \{\left \{y(x)\to \text {InverseFunction}\left [-\frac {\sqrt {\text {\#1}^2+1}}{\text {\#1}}-\frac {1}{\text {\#1}}+\sinh ^{-1}(\text {\#1})\& \right ][-x+c_1]\right \},\left \{y(x)\to \text {InverseFunction}\left [-\frac {\sqrt {\text {\#1}^2+1}}{\text {\#1}}+\frac {1}{\text {\#1}}+\sinh ^{-1}(\text {\#1})\& \right ][x+c_1]\right \}\right \}$ Maple : cpu = 0.026 (sec), leaf count = 85

$\left \{ x- \left ( y \left ( x \right ) \right ) ^{-1}-{\frac {1}{y \left ( x \right ) } \left ( \left ( y \left ( x \right ) \right ) ^{2}+1 \right ) ^{{\frac {3}{2}}}}+y \left ( x \right ) \sqrt { \left ( y \left ( x \right ) \right ) ^{2}+1}+{\it Arcsinh} \left ( y \left ( x \right ) \right ) -{\it \_C1}=0,x+{\frac {1}{y \left ( x \right ) } \left ( \left ( y \left ( x \right ) \right ) ^{2}+1 \right ) ^{{\frac {3}{2}}}}-y \left ( x \right ) \sqrt { \left ( y \left ( x \right ) \right ) ^{2}+1}-{\it Arcsinh} \left ( y \left ( x \right ) \right ) - \left ( y \left ( x \right ) \right ) ^{-1}-{\it \_C1}=0 \right \}$